2000
DOI: 10.1093/aje/152.10.950
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative Risk of Breast Cancer to Age 70 Years According to Risk Factor Status: Data from the Nurses' Health Study

Abstract: Because of the temporal relations between reproductive risk factors and incidence of breast cancer, the authors developed a nonlinear Poisson regression that accounts for time and summarizes risk to age 70 years. Reproductive risk factors, benign breast disease, use of postmenopausal hormones, weight, and alcohol intake were evaluated as risk factors. Among 58,520 women aged 30-55 years in 1980, followed through June 1, 1994, 1,761 incident invasive breast cancer cases were identified. All risks are multivaria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

16
288
2
5

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 377 publications
(311 citation statements)
references
References 25 publications
16
288
2
5
Order By: Relevance
“…As reported in several other studies (Collaborative Group on Hormonal Factors in Breast Cancer, 1997; Colditz and Rosner, 2000;Schairer et al, 2000), current use of hormone replacement therapy (HRT) was associated with an increased risk of breast cancer, and the risk increased with the number of HRT prescriptions. We were not able to analyse reproductive risk factors because these data are not coded routinely in the GPRD.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…As reported in several other studies (Collaborative Group on Hormonal Factors in Breast Cancer, 1997; Colditz and Rosner, 2000;Schairer et al, 2000), current use of hormone replacement therapy (HRT) was associated with an increased risk of breast cancer, and the risk increased with the number of HRT prescriptions. We were not able to analyse reproductive risk factors because these data are not coded routinely in the GPRD.…”
Section: Discussionmentioning
confidence: 81%
“…It would therefore be inappropriate to conclude that statin treatment lowered the risk of breast cancer in our study, simply because women treated for hyperlipidaemia were at no greater risk than normolipemic women. There was no effect of the duration of current statin use on the risk of breast cancer, and the 95% confidence intervals for relative risk of breast cancer among women with untreated hyperlipidaemia and current statin users overlap considerably.As reported in several other studies (Collaborative Group on Hormonal Factors in Breast Cancer, 1997;Colditz and Rosner, 2000;Schairer et al, 2000), current use of hormone replacement therapy (HRT) was associated with an increased risk of breast cancer, and the risk increased with the number of HRT prescriptions. We were not able to analyse reproductive risk factors because these data are not coded routinely in the GPRD.…”
mentioning
confidence: 81%
“…Our study allowed for deeper analysis of the sources and mechanisms causing this heterogeneity. We used a biologically motivated model that was specified by cancer subtype (ductal and lobular), race, stage, grade, and hormone receptor status, thus extending existing breast carcinogenesis models [6,[15][16][17][18][19]. The results demonstrated that grade plays the primary role in breast cancer heterogeneity, with ER/ PR status ''strengthening'' the grade effect.…”
Section: Discussionmentioning
confidence: 99%
“…All analyses were controlled for age (continuous), body mass index (weight in kg 2 height in m, continuous), smoking (never, ever), age at menarche (continuous), parity (0, 1, 2, 3 or more), and history of breast cancer in the mother. The case-only analyses were additionally controlled for menopausal status, age at menopause (continuous), and cumulative years of hormone replacement therapy (continuous) (Colditz and Rosner, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…first within women from the population sample and then within women with breast cancer) and therefore avoiding problems of differential misclassification often encountered in case-control studies. Furthermore, the case-only design allowed to control for menopausal status, age at menopause, and cumulative years of hormone replacement therapy in the multivariable analysis as recently suggested (Colditz and Rosner, 2000).…”
Section: Discussionmentioning
confidence: 99%